Comparative Effectiveness of Two Interventions to Increase Colorectal Cancer Screening for Those at Increased Risk Based on Family History: Results of a Randomized Trial - Paskett, Electra D; Bernardo, Brittany M; Young, Gregory S; Katz, Mira L; Reiter, Paul L; Tatum, Cathy M; Oliveri, Jill M; DeGraffinreid, Cecilia R; Gray, Darrell Mason; Pearlman, Rachel; Hampel, Heather (Cancer epidemiology, biomarkers & prevention, 2020)
First-degree relatives (FDR) of patients with colorectal cancer are at risk for colorectal cancer, but may not be up to date with colorectal cancer screening. We sought to determine whether a one-time recommendation about needing colorectal cancer screening using patient navigation (PN) was better than just receiving the recommendation only. Participants were FDRs of patients with Lynch syndrome-negative colorectal cancer from participating Ohio hospitals. FDRs from 259 families were randomized to a website intervention (528 individuals), which included a survey and personal colorectal cancer screening recommendation, while those from 254 families were randomized to the website plus telephonic PN intervention (515 individuals). Primary outcome was adherence to the personal screening recommendation (to get screened or not to get screened) received from the website. Secondary outcomes examined who benefited from adding PN. At the end of the 14-month follow-up, 78.6% of participants were adherent to their recommendation for colorectal cancer screening with adherence similar between arms ( = 0.14). Among those who received a recommendation to have a colonoscopy immediately, the website plus PN intervention significantly increased the odds of receiving screening, compared with the website intervention (OR: 2.98; 95% confidence interval, 1.68-5.28). Addition of PN to a website intervention did not improve adherence to a colorectal cancer screening recommendation overall; however, the addition of PN was more effective in increasing adherence among FDRs who needed screening immediately. These findings provide important information as to when the additional costs of PN are needed to assure colorectal cancer screening among those at high risk for colorectal cancer.